0

I am trying to get the 3rd equality (from the top, the equations for delta \phi^i) to align.

enter image description here

\begin{align*}
U(x)  &= e^{i\theta^a(x)T^a}             &  U(x) &= e^{-\theta^a(x)(t_a)^i{}_j}  \\ 
 [T^a,T^b] &= if^{abc}T^c  &  [t^a,t^b] &= f_{ab}{}^c t^c \\
\delta \phi_i &= i\theta^a(T^a)_{ij} \phi_j  &  \begin{split}
 \delta \phi^i &= -\theta^a(t_a)^i{}_j \phi^j \\
&= -\theta^af_{aj}{}^i \phi^j \\
&= \theta^af_{ja}{}^i \phi^j
\end{split} \\
A_\mu  &= A_\mu{}^a T^a            &  A_\mu &=  A_\mu{}^a t_a \\ 
A_\mu  &\rightarrow U(x) A_\mu U(x)^{-1} -
\frac{i}{g} [\partial_\mu U(x)] U(x)^{-1} &  A_\mu  &\rightarrow U(x) A_\mu U(x)^{-1} -
\frac{1}{g} [\partial_\mu U(x)] U(x)^{-1}
\end{align*}

Here are two related questions

How to align a set of multiline equations

Aligning two multiline equations

2

Use aligned with [t] option?

Is this what you're after?

enter image description here

\documentclass{extarticle}
\usepackage{amsmath}
\begin{document}
\begin{align*}
    U(x)  &= e^{i\theta^a(x)T^a}             &  U(x) &= e^{-\theta^a(x)(t_a)^i{}_j}  \\ 
    [T^a,T^b] &= if^{abc}T^c  &  [t^a,t^b] &= f_{ab}{}^c t^c \\
    \delta \phi_i &= i\theta^a(T^a)_{ij} \phi_j  &  
    \delta \phi^i & 
    \begin{aligned}[t]
         &= -\theta^a(t_a)^i{}_j \phi^j \\
        &= -\theta^af_{aj}{}^i \phi^j \\
        &= \theta^af_{ja}{}^i \phi^j
    \end{aligned} \\
    A_\mu  &= A_\mu{}^a T^a            &  A_\mu &=  A_\mu{}^a t_a \\ 
    A_\mu  &\rightarrow U(x) A_\mu U(x)^{-1} -
    \frac{i}{g} [\partial_\mu U(x)] U(x)^{-1} &  A_\mu  &\rightarrow U(x) A_\mu U(x)^{-1} -
    \frac{1}{g} [\partial_\mu U(x)] U(x)^{-1}
\end{align*}
\end{document}
  • Brilliant work! Thank you :) – Lopey Tall May 4 '20 at 12:01
0
  • you can write your equation with use only align* environment
  • equation is wider than text width, consequently it spill out from right text border:

enter image description here

(red lines indicate page layout)

\documentclass{extarticle}
\usepackage{amsmath}
%---------------- show page layout. don't use in a real document!
\usepackage{showframe}
\renewcommand\ShowFrameLinethickness{0.15pt}
\renewcommand*\ShowFrameColor{\color{red}}
%---------------------------------------------------------------%

\begin{document}
    \begin{align*}
U(x)        
    & = e^{i\theta^a(x)T^a} &  U(x)         & = e^{-\theta^a(x)(t_a)^i{}_j}  \\
[T^a,T^b]   
    & = if^{abc}T^c         &  [t^a,t^b]    & = f_{ab}{}^c t^c  \\
\delta\phi_i    
    & = i\theta^a(T^a)_{ij}\phi_j   &
            \delta \phi^i   & = -\theta^a(t_a)^i{}_j \phi^j     \\ 
    &&                      & = -\theta^af_{aj}{}^i \phi^j      \\
    &&                      & = \theta^af_{ja}{}^i \phi^j       \\
A_\mu  
    & = A_\mu{}^a T^a       &  
            A_\mu           &=  A_\mu{}^a t_a               \\
A_\mu  
    & \rightarrow U(x) A_\mu U(x)^{-1} - \frac{i}{g} [\partial_\mu U(x)] U(x)^{-1} &  
                    A_\mu   & \rightarrow U(x) A_\mu U(x)^{-1} 
                                        - \frac{1}{g} [\partial_\mu U(x)] U(x)^{-1}
    \end{align*}
\end{document}
  • this problem you can solve on two ways, for example:
    • enlarge text area for example with use of the `geometry package
    • break last equation in each column

enter image description here

\documentclass{extarticle}
\usepackage{amsmath}
%---------------- show page layout. don't use in a real document!
\usepackage{showframe}
\renewcommand\ShowFrameLinethickness{0.15pt}
\renewcommand*\ShowFrameColor{\color{red}}
%---------------------------------------------------------------%

\begin{document}
    \begin{align*}
U(x)        
    & = e^{i\theta^a(x)T^a} &  U(x)         & = e^{-\theta^a(x)(t_a)^i{}_j}  \\
[T^a,T^b]   
    & = if^{abc}T^c         &  [t^a,t^b]    & = f_{ab}{}^c t^c  \\
\delta\phi_i    
    & = i\theta^a(T^a)_{ij}\phi_j   &
            \delta \phi^i   & = -\theta^a(t_a)^i{}_j \phi^j 
                              = -\theta^af_{aj}{}^i \phi^j      \\
    &&                      & = \theta^af_{ja}{}^i \phi^j       \\
A_\mu  
    & = A_\mu{}^a T^a       &  
            A_\mu           &=  A_\mu{}^a t_a                   \\
A_\mu  
    & \rightarrow U(x) A_\mu U(x)^{-1}  &   
                    A_\mu   & \rightarrow U(x) A_\mu U(x)^{-1}  \\
    &\qquad - \frac{i}{g} [\partial_\mu U(x)] U(x)^{-1} & 
                            &\qquad - \frac{1}{g} [\partial_\mu U(x)] U(x)^{-1}
    \end{align*}
\end{document}

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.